PENGARUH JENIS MULSA TERHADAP PERTAMBAHAN VOLUME AKAR DAN KARAKTER FISIOLOGIS TIGA VARIETAS PADI GOGO - Kusbiantoro, Dedi; Hanum, Chairani; Asbur, Yenni; Purwaningrum, Yayuk; Alfisar, Fiqi; Sihaloho, Martha Adiwaty (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
Gogo rice is one of the food crops that has the potential to be developed in national rice is becoming increasingly important, this is due to the decreasing rice field area, while the population growth rate is getting higher. Field experiments were carried out on the land of the Faculty of Agriculture, Islamic University of North Sumatra from May to August 2021. The aim is to determine the effect of mulch type on root volume, plant growth rate and net assimilation rate of gogo rice plants. The research method used was a Factorial Group Random Design with three different types of mulch as treatment, namely without mulch, black plastic mulch, Asystasia gangetica mulch, straw mulch. The varieties used are IPB8, IPB9 and Red Sigambiri. The treatment combination consists of 12 combinations in three repetitions. The results showed that mulch and varietal treatment had a real effect on root volume, while on plant growth rate and net assimilation rate had no real effect. Keywords: rice gogo, mulch, varieties